Relationship between oral transit time and functional performance in motor neuron disease - Bárbara Carolina Brandão; Magali Aparecida Orate Menezes da Silva; Paula Cristina Cola; Roberta Gonçalves da Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT Oral phase swallowing impairment in motor neuron disease (MND) is caused by tongue weakness, fasciculation and atrophy, which may compromise oral transit time and total feeding time. Objective: To describe and correlate total oral transit time (TOTT) with functional performance in MND using different food consistencies. Methods: The study was conducted on 20 patients with MND, regardless of type or duration of the disease, of whom nine were excluded due to issues on the videofluoroscopic swallowing images. The remaining 11 patients (nine men and two women) ranged from 31 to 87 years of age (mean: 57 years) with scores on the Penetration Aspiration Scale ranging from ≤ 2 to ≤ 4. The Amyotrophic Lateral Sclerosis Functional Rating Scale - revised questionnaire was applied to classify individuals according to global, bulbar and bulbar/respiratory parameters. Videofluoroscopy of swallowing using 5ml of different consistencies was performed and a quantitative temporal analysis of the TOTT was carried out with the aid of specific software. Results: There was a wide variation in the TOTT within the same food consistency among MND patients. There was a correlation between the TOTT and overall functional performance for the thickened liquid consistency (r = −0.691) and between the TOTT and bulbar performance for the pureed consistency (r = −0.859). Conclusion: Total oral transit time in MND varies within the same food consistency and the longer the TOTT, regardless of food consistency, the lower the functional performance in MND.